2011
DOI: 10.2984/65.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of the Name Chaetomorpha vieillardii (Kütz.), n. Comb., for a Large-Celled Tropical Chaetomorpha (Chlorophyta)

Abstract: Type material of Bangia vieillardii Kü tz. from New Caledonia has been studied and determined to belong to the green algal genus Chaetomorpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…1845: 204. Wynne (2011b) reported that the name Chaetomorpha crassa has been misapplied to Caribbean material.…”
Section: Excluded Taxonmentioning
confidence: 99%
“…1845: 204. Wynne (2011b) reported that the name Chaetomorpha crassa has been misapplied to Caribbean material.…”
Section: Excluded Taxonmentioning
confidence: 99%
“…Growth is diffuse, producing cylindrical to barrel-shaped to rarely oval cells 20 -5000 um in diameter, generally consistent within species. One of the most significant characteristics in the delimitation of species within the genus Chaetomorpha is the thickness of the filaments, the stiffness of the thallus and the shape of the segments [76]. According to [77], Chaetomorpha aerea has been treated as a synonym of Chaetomorpha linum (O. F. Müller) Kützing by several authors [43] [78] [79].…”
Section: The Presence Of Ceratodictyon Varibile Was Previously Recordmentioning
confidence: 99%
“…2c, d, e) ha sido registrada en Cuba y Florida y tiende a ser confundida con Ulva rigida; 2) El nombre de Chaetomorpha crassa (C. Agardh) Kützing ha sido aplicado a especímenes flotantes o epifitos con filamentos gruesos que habitan en los mares tropicales y templados de América; de acuerdo con Wynne (2011b), estos especímenes corresponden a Chaetomorpha vieillardii (Figs. 3c, d), especie que se distribuye en Brasil, Filipinas y Nueva Caledonia, mientras que en México no ha sido registrada debido a que probablemente es confundida con Ch.…”
Section: Nuevos Registrosunclassified